Registration of Diagnoses in the Danish National Registry of Patients - Jürgensen, H. J.; Frølund, C.; Gustafsen, J.; Mosbech, H.; Guldhammer, Birgitte; Mosbech, J. (Methods of Information in Medicine, 1986)
The data recorded in the National Registry of Hospitalized Patients in Denmark (Landspatient-registeret [LPR]) are based on reports from the somatic departments of hospitals throughout the country. For the purpose of evaluating the quality of these data, information from LPR concerning patient diagnoses was compared with corresponding information in the records from 924 consecutive admissions to the Frederiksborg County Hospital, Hiller0d. The diagnoses in these records were registered and given priority based on predetermined criteria for selection of primary and secondary diagnoses, respectively. For each hospitalized case a total of 4 primary and 4 secondary diagnoses might be registered. In order to show the variation in choice of diagnoses between physicians, all records from the two medical departments and 10% from the remaining departments were revised by two different physicians. In the medical “block” (medical departments B and F, and the departments of physical medicine, paediatrics, and neurology), there was agreement between the two physicians on at least one of the maximally 4 primary diagnoses which could be registered in 92% of the cases (2-digit code). For the surgical “block” (the departments of parenchymal surgery, orthopaedic surgery, gynaecology, and otology), the corresponding figure was 95%. If the two coders were in agreement on at least one primary diagnosis, this was identical with LPR’s primary diagnosis in 76% of the cases in the medical “block” and 85% of the cases in the surgical “block” (2-digit code). However, in the case of 15% of the medical and 7% of the surgical cases, the primary diagnosis, on which the two coders were in agreement, was not recorded at all by LPR (3-digit code).It is to be emphasized that a certain variation between different physicians in their choice of diagnoses cannot be eliminated. In conclusion, the level of agreement between LPR and the study material found in the present study is in general satisfactory if LPR’s function as a basis of information for policy making in the hospital sector is taken into consideration. On the other hand, agreement (especially on medical records) is presumably not good enough in LPR to be used for research purposes.
Keywords: Hospital Statistics; Quality Control; Evaluation of Diagnostics; Patient Registry